MENJADI WIRAUSAHA MUDA (YOUNG ENTREPRENEUR) SUATU PENDEKATAN ANALISIS SWOT (KASUS LULUSAN PERGURUAN TINGGI DI KABUPATEN OKU - M u n a j a t . (Universitas PGRI Palembang, 2013)
This research is to find out about the identification the strength, weakness, opportunity and threath to make young entrepreneur in Ogan Komering Ulu region and also about the strategy. From the research, its noticed that the internal factors are academic ability to knows about the entrepreneur world theory, thingking ability, thingking systematic, and physic ability. Otherwhile, as the weakness factors are mental problem (ego and afraid to take a risk), the minim curriculum didn’t fit with skill entrepreneurship and management, min equity bussines, and not active to follow the mentoring, and seminary about entrepreurship. The eksternal factors are opportunity to decrease the unemployment, to increase PAD, stressing criminality region, didn’t have any family responsibility, and not enough the bussines opportunity in OKU. As the threaths are problem from parent, familiy, and people nearly that still wants to work as PNS and employee, and min the instruction to open the bussines caused wrong direction in opening the bussines. The alternative strategies to becoming the young entrepreneur in OKU are SO, ST, WO and WT strategy. Key words : Young entrepreneur, SWOT analyzis, Internal factor, Eksternal factor